Simulation-Based Strategies Co-Designed With Young Adults for Sickle Cell Disease Self-Management - Dora L. Clayton-Jones; Sylvia Pena; Kristin Haglund; Joan P. Totka; Abir K. Bekhet; Lee Za Ong; Janet Lucas; Edward Jenkins; Anne M. Costello; James Griffin; Grainne Kilroy Ferlmann; Betty S. Pace (Western Journal of Nursing Research, 2026)
Background: Young adults living with sickle cell disease (SCD) face complex self-management challenges during care-seeking. Developmentally appropriate, experiential interventions remain limited. Interventions to prepare young adults for emotionally charged real-world situations such as emergency department encounters, peer communication, and independent decision-making are needed. Purpose: To describe the co-design of a simulation-based self-management intervention for young adults living with SCD and conduct evaluation of 6 intervention implementation parameters: necessity, acceptability, feasibility, safety, fidelity, and preliminary effectiveness. Methods: Using mixed-methods design guided by community-based participatory research and human-centered design, young adults living with sickle cell disease, caregivers, and community stakeholders co-created a simulation-based intervention with 3 video-supported scenarios with structured role-play and facilitated debriefing. Thirty participants aged 18 to 20 years completed pre–post surveys and participated in post-intervention focus groups. Quantitative data were analyzed using paired-sample t -tests, and qualitative data were analyzed using inductive thematic analysis. Results: Implementation evaluation demonstrated strong outcomes across all parameters. Participants indicated that the intervention is necessary, acceptable, feasible, safe, effective, and has high fidelity. Statistically significant improvements in self-efficacy were observed post-intervention. Qualitative findings supported these outcomes, with participants reporting increased confidence in emergency department advocacy, communication with healthcare providers and peers, and proactive self-management behaviors. Conclusion: Evaluation of the 6 intervention implementation parameters supports the use of simulation-based self-management intervention for young adults living with sickle cell disease. Integrating community voices and experiential learning strategies enhances self-efficacy, promotes meaningful behavior change, and improves real-world health management readiness during the critical period of emerging adulthood.